2020
DOI: 10.3390/su12187524
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Sustainability in Food Systems: Perspectives from Agroecology and Social Innovation

Abstract: Food security faces many multifaceted challenges, with effects ranging far beyond the sectors of agriculture and food science and involving all the multiscale components of sustainability. This paper puts forward our point of view about more sustainable and responsible approaches to food production research underlying the importance of knowledge and social innovation in agroecological practices. Increased demand for food worldwide and the diversification of food choices would suggest the adoption of highly pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 113 publications
0
31
0
1
Order By: Relevance
“…Agro-ecological methods are often low-tech and labor-intensive, but are suitable for urban and peri-urban agriculture and horticulture, where farmland is a scarce resource [29]. A previous study on diversified farming systems as a social and economic basis to foster social-ecological conversion concluded that a diversity of knowledge and practices makes a promising alternative to the uniformity of industrialized agriculture when it comes sustaining and regenerating eco-system services, while comparing well with industrialized agriculture in terms of productivity (Marchetti et al [30]).…”
Section: Discussionmentioning
confidence: 99%
“…Agro-ecological methods are often low-tech and labor-intensive, but are suitable for urban and peri-urban agriculture and horticulture, where farmland is a scarce resource [29]. A previous study on diversified farming systems as a social and economic basis to foster social-ecological conversion concluded that a diversity of knowledge and practices makes a promising alternative to the uniformity of industrialized agriculture when it comes sustaining and regenerating eco-system services, while comparing well with industrialized agriculture in terms of productivity (Marchetti et al [30]).…”
Section: Discussionmentioning
confidence: 99%
“…The ABC Plan is analysed from the perspective of the conceptual framework proposed. We followed the steps of some studies conducted previously, such as Marchetti L. et al and Pólvora A. et al [38,39].…”
Section: Methodsmentioning
confidence: 99%
“…Hohnwald et al (2015) tested this model in practice and found that it represents a promising and ecologically sustainable alternative for smallholders. De facto, the importance of diversified farming systems incorporating farmer preferences and knowledge are currently increasing (Marchetti et al 2020). Amézquita et al (2005), comparing different silvopastoral systems with native forest and degraded pasture, reported higher levels of SOC and concluded that they can constitute a viable economic alternative to farmers.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%